2006
DOI: 10.4049/jimmunol.177.1.437
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Proteins fromMycobacterium tuberculosisGain Access to the Cytosolic MHC Class-I Antigen-Processing Pathway

Abstract: CD8+ T cells play an important role in the host response to infection with Mycobacterium tuberculosis (Mtb). Mtb resides in an arrested phagosome that is phenotypically similar to an early endosome. The mechanisms by which Mtb-derived Ags gain access to the HLA-I-processing pathway are incompletely characterized. Studies with CD8+ T cell lines have suggested that Mtb Ags gain access to the HLA-I pathway in an alternate vacuolar pathway that is both brefeldin A (BFA) and TAP independent. To define the requireme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
62
3
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 35 publications
3
62
3
1
Order By: Relevance
“…This is particularly relevant as the vacuolar pathway appears less efficient than the phagosome-to-cytosol pathway in the generation of immune responses in vivo (30). It should be noted that the absence of RD1-encoded proteins does not appear to affect the capacity of DCs to present secreted M. tuberculosis Ags to human CD8 T cells via the cytosolic pathway (35), however detailed comparison of the precise Ag processing and presentation mechanisms used to activate either BCG-or M. tuberculosis-reactive CD8 T cells has yet to be performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly relevant as the vacuolar pathway appears less efficient than the phagosome-to-cytosol pathway in the generation of immune responses in vivo (30). It should be noted that the absence of RD1-encoded proteins does not appear to affect the capacity of DCs to present secreted M. tuberculosis Ags to human CD8 T cells via the cytosolic pathway (35), however detailed comparison of the precise Ag processing and presentation mechanisms used to activate either BCG-or M. tuberculosis-reactive CD8 T cells has yet to be performed.…”
Section: Discussionmentioning
confidence: 99%
“…In the vacuolar model, peptides generated in the phagosome are loaded on to MHC class I molecules and processing does not require TAP or trafficking through the endoplasmic reticulum. Ags such as OVA can be presented to CD8 T cells by the two pathways (31,32), and both cytosolic and alternative models of Ag presentation have been shown to contribute to the recognition of mycobacterial Ags (33)(34)(35). It is possible that both these pathways contribute to CD8 T cell activation after BCG or M. tuberculosis infection, and the greater Ag load available for MHC class I loading after infection with M. tuberculosis results in improved T cell priming.…”
Section: Discussionmentioning
confidence: 99%
“…A more interesting possibility is that the ESX-1 system functions in a manner similar to type III or type IV secretion systems of other pathogenic bacteria for delivery of bacterial effectors directly into the cytosol of infected macrophages (44). Recently, it was shown that CFP-10 presentation by MHC class I requires components specific to the cytosolic Ag-processing pathway, providing evidence that CFP-10 gains access to the cytosol during infection (13). Additional evidence that M. tuberculosis is capable of accessing cytosolic signaling pathways was provided by Ferwerda et al (38), who showed that nod proteins are involved in the response to infection with M. tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…M. tuberculosis, unlike L. monocytogenes, is found exclusively in membrane bound compartments, suggesting that type I IFN production proceeds through a different pathway. Lewinsohn et al (13) showed that culture filtrate protein-10 (CFP-10), a protein secreted by the ESX-1 system of M. tuberculosis, gains access to the cytosol during infection and is presented by the MHC class-I Ag processing pathway, demonstrating the possibility that products from M. tuberculosis may gain access to cytosolic signaling receptors during infection.…”
mentioning
confidence: 99%
“…It is likely that NLR ligands are able to access the macrophage cytosol. Possible mechanisms for the cytosolic localization and recognition of M. tuberculosis NLR ligands include the rupture of phagosomes due to the particulate nature of M. tuberculosis antigens and the release of PAMPs into the cytosol, as well as entry of M. tuberculosis components into the macrophage cytoplasm (27,57,62). This may be mediated in part by ESAT-6, which is implicated in mediating membrane damage and has been reported to be required for activation of caspase-1 and the NLRP3 inflammasome (37).…”
Section: Discussionmentioning
confidence: 99%